Wymiar lewica–prawica w Polsce – podziały ideologiczne w polskim społeczeństwie - Pająk-Patkowska, Beata (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
Despite a certain degree of chaos characterizing the Polish political arena, Polish society can be said to be capable of relatively accurate categorization of political parties with respect to their position in the left – right spectrum; two thirds of society are also able to identify their own views in this respect. What differentiates Polish society from Western European societies, though, is the lack of correlation between ones’position in the social structure and ideology, as well as the negligible importance of economic matters in one’s identification as a left – right winger. The emergence of two strong political parties referring to themselves as right-wing (Civic Platform – PO and Law and Justice – PiS), accompanied by the weakening of the left of the political arena in Poland has resulted in this tendency becoming even stronger.